PRODUKTIVITAS ANGKUT TRUK DAN TRUK SEMI-TRAILER - Apul Sianturi; Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1985)
An investigation on log hauling by truck and semi-trailer truck has been carried out at 14 concession  areas in Sumatera and  5 concession  areas in South  Kalimantan in 1980  and  1981. The  investigation  comes to  the following conclussions :1.    Logging Companies in Riau, Jambi and South Sumatera  use poorly constructed forest roads without any graveling.2.    On the other  hand  those in South Kalimantan are relatively good  graveled  roads.3.    Effective  hauling  outputs of  trucks range from 91 to 361 m3km/round trip hour, with an average of 247 m3 km/round  trip hour, and those of semi-trailer  truck  from  265  to 841 m3 km/round  trip hour,  with an average of 494 m3 km/round  trip hour.There is pronounced linier relation  between hauling  distance and round trip time.